Biological control agents of the number of Halyomorpha halys Stål - Irina S. Agasyeva; Maria V. Nefedova (Аграрная наука Евро-Северо-Востока)
Research aimed at studying the control of the number of pests of many agricultural crops – Halyomorpha halys Stål, was carried out during 2018-2020 on the territory of the Central zone of Krasnodar Krai. In the experiments, there were used individuals of a brown marmorated stink bug, caught by hand and using a pheromone trap at different stations (tree and shrub vegetation, soybean crops). In 2020, the dynamics of the abundance of the brown marmorated stink bug was monitored since the end of May (the time of the appearance of the first individuals of H. halys) to the third decade of October. Among the natural entomophages in Krasnodar Krai, two species of parasitic insects were found: Pediobius cassidae Erdos. (Hymenoptera: Eulophidae) and Anastatus bifasciatus Geoffroy (Hymenoptera: Eupelmidae), infecting about 5-10 % of H. halys eggs in the field, which did not significantly affect the abundance of the brown marmorated stink bug. In the laboratory, essential oils from several botanical families were tested: Umbelliferae, Compositae, Abies. Essential oils of wormwood, coriander and Siberian fir showed a toxic effect against the brown marmorated stink bug; the death of adults on the tenth day was 100, 95.0 and 93.7 %, respectively. Also, on the soybean crops of the Arleta variety, field tests were carried out to study the efficacy of bio-rational preparations Biostop, P and an experimental preparation developed at the Federal State Budgetary Scientific Institution "Federal Research Center of Biological Plant Protection" (FSBSI FRCBPP). The experimental preparation of FRCBPP caused the death of 64.2 % of individuals of H. halys, Biostop, P – 70.1 %.